The Experiences of Indigenous Health Workers Enrolled in a Bachelor of Nursing at a Regional Australian University. (March 2015) - Stuart, Lynne; Gorman, Don
In Australia, the Indigenous health workforce is in urgent need of Indigenous health professionals with credible qualifications in higher education that they can draw upon when attempting to influence government policies and health strategies. One way that this can be addressed is by Indigenous health workers gaining a Bachelor of Nursing degree. This paper reports on a study that focused on the experiences of Indigenous health workers, and how they have met and overcome significant and specific challenges in higher education to become registered nurses. The active involvement of five Indigenous health worker participants is described and their experiences discussed in relation to cross-cultural awareness; financial, cultural, academic, family and peer support; stress factors; staying motivated; and the many and varied issues that impact on confidence levels. The paper provides a number of recommendations for improving the student support mechanisms for Indigenous health workers to overcome barriers to successfully participating in, and graduating from, higher education degree courses.